Interpretacja statystyk w artykułach naukowych - wskazówki dla praktyków = The interpretation of the statistical data in scientific papers - advices for practitioners - Budzicz, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains information how to interpret statistical data: statistical significance, effect size and confidence intervals. Several heuristics are given how to usefully interpret the magnitude of the correlation Pearson's r, Cohen's d and relative risk. The vast majority of other effects is a derivative of the aforementioned. In addition, I also show the limitations of selected indicators, especially statistical significance. This article is intended as an aid especially for psychologists practitioners.
Keywords: wielkość efektu; istotność statystyczna; przedziały ufności; interpretowanie danych statystycznych; effect size; statistical significance; confidence interval; interpretation of statistical data